Biology Teachers’ Awareness of the Concepts and Applications of Deep Learning in Senior High Schools - Slamet Suyanto; RAHMANIA PAMUNGKAS; Wenny Pinta Litna Tarigan (Yayasan Nurul Yakin Bunga Tanjung, 2026)
is study examines senior high school biology teachers’ understanding of deep learning and the extent to which its principles are reflected in classroom planning and practice. An exploratory descriptive mixed-methods design was used with 20 biology teachers from public and private schools in Sleman Regency, Indonesia. Data were collected through a questionnaire on conceptual, practical, and reflective understanding, semi-structured interviews, written reflections, and document analysis of lesson plans, student worksheets, and related teaching materials. Quantitative data were analyzed descriptively, while qualitative data were analyzed through reflexive thematic analysis and rubric-based document review. Findings show that 15% of teachers were in the low category, 45% in the moderate category, and 40% in the high category. Teachers generally associated deep learning with active learning, inquiry, higher-order thinking, and project-based activities. However, documentary evidence showed that transfer-oriented tasks, explicit student agency, and authentic assessment were less consistently planned than contextual tasks and higher-order questioning. Time pressure, assessment workload, student heterogeneity, and limited institutional support were major constraints. The results suggest that teachers’ readiness is promising but uneven, and that professional development should emphasize outcome-task-assessment alignment, transfer-oriented learning, and feasible authentic assessment in biology instruction